Role of tissue transglutaminase in gliadin binding to reticular extracellular matrix and relation to coeliac disease autoantibodies. - Uhlig, H; Osman, A; Tanev, I; Viehweg, J; Mothes, T (1998)
On different tissue sections, binding of gliadin to reticular matrix components was observed which was Ca2+-dependent, inhibited by Cu2+ and Zn2+ ions, by putrescine, and by preincubation with antibodies against tissue transglutaminase (tTG) suggesting that binding of gliadin is mediated by tTG. tTG was able to bind to gliadin and fibronectin fixed to microplates. Furthermore, tTG mediated binding of gliadin to fibronectin coated to microplates. On tissue sections, treatment with sera containing coeliac disease autoantibodies yielded staining patterns very similar to that of bound gliadin. Dual label experiments by means of conventional and laser scanning microscopy revealed that most of autoantibody binding sites are matched by bound gliadin. However, lack of competition between gliadin and autoantibody binding hints to ligands in very close vicinity of this enzyme. Furthermore, there were several autoantibody binding regions which did not bind gliadin. This implies the existence of further autoantigenic epitopes not related to tTG.